AN IMPROVED ENRICHMENT PROCEDURE FOR THE ISOLATION OF YERSINIA-ENTEROCOLITICA AND RELATED SPECIES FROM MILK - Landgraf, M.; Iaria, S. T.; Falcao, D. P. (Int Associação Milk Food Environmental Sanitarians, Inc, 1993)
A new enrichment procedure is proposed to improve the isolation of Yersinia enterocolitica and related species from milk. This procedure uses tryptic soy broth plus Polymyxin (5 IU/ml) and Novobiocin (10 mug/ml) - TSPN broth - incubated at 18-degrees-C for 3 d. Using raw milk and pasteurized milk inoculated with Yersinia strains, the efficiency of this procedure was compared to that of SB broth (sorbitol bile salts broth) incubated at 4-degrees-C for up to 21 d. Despite of the presence of antibiotics in TSPN broth, there were difficulties in recovering Yersinia organisms. Nevertheless, TSPN broth incubated at 18-degrees-C for 3 d showed better efficiency than that other method. In pasteurized milk samples, TSPN medium at 18-degrees-C for 3 d gave better results than the SB broth at 4-degrees-C for 7 d, showing that the proposed procedure is the preferable one due to the shorter period of incubation.